Detection of Hepatitis C Virus RNA in blood and saliva of transfusion-dependent thalassemia patients diagnosed with Hepatitis C - Behzad Hooshmand; Seyed Moayed Alavian; Farnaz Kouhestani; Maryam Firouzmandi; Saeed Reza Motamedian (Contemporary Clinical Dentistry, 2018)
Background: The aim of the current study was to detect hepatitis C virus (HCV) RNA in blood and saliva of a population of patients with thalassemia who have HCV antibody in their serum. Materials and Methods: In this cross-sectional study, blood and saliva samples were collected and were analyzed with quantitative reverse transcription polymerase chain reaction (RT-PCR) for the detection of HCV RNA. In addition, liver-related blood tests were performed, and patients' medical history was recorded. Data were analyzed by independent samples t-test and Chi-square with a significant level of 0.05. Results: Overall, 62 adult patients (29 males and 33 females) were included. Most (87%) of the patients had major thalassemia and genotype 1a was the most common (42%) type. HCV RNA was detected in 71 and 16% of blood and saliva samples, respectively. HCV RNA was detected more in female patients (31%) (P = 0.003) and in intermediate thalassemia (50%) (P < 0.005). The mean age of the patients with positive saliva was almost 10 years older (P < 0.001), and the mean number of blood transfusion was fewer in positive saliva group (P = 0.037). The sensitivity, specificity, and positive and negative predictive values of saliva PCR was calculated to be 18%, 88%, 80%, and 69%, respectively. Conclusion: Saliva contained HCV RNA in 16% of the assessed population. The probability of detection of HCV RNA in saliva increased in older patients, less number of blood transfusions, females and intermediate thalassemia. Saliva RT-PCR demonstrated low sensitivity and high specificity with high positive predictive value in the assessed population.